Top 100 Diagnoses in Neurology. Core Features, Synopses, Illustrations and Questions for Rapid Review and Retention: reference for clinicians - Kister, I. Ilya (Wolters Kluwer, 2021)
"In arriving at a clinical diagnosis, think of the five most common findings (either historical, physical findings, or laboratory) found in a given disorder. If at least three of these five are not present in a given patient, the diagnosis is likely to be wrong". (C. Miller Fisher). Building on this precept from the great 20th-century neurologist C. Miller Fisher, Drs. Ilya Kister and José Biller have identified the five most common findings for the 'top 100' most common and important neurologic syndromes and disorders. The unique format of Top 100 Diagnoses in Neurology includes synopses that tie together the core disease features, illustrations and study questions for each entry, making this book an excellent tool for building a firm knowledge base in neurology and a quick reference for clinicians - neurologists and general practitioners alike. Covers the five core features of 100 of the most important neurologic syndromes and disorders, including polyneuropathies, neurologic vision disorders, movement disorders, epilepsy syndromes, multiple sclerosis, autism spectrum disorder, cerebral palsy, opioid overdose, brain tumors, and much more. Icons are used to identify neurologic emergencies and specify disease prevalence (common, rare, very rare). Includes brief introductions to each section that provide an essential clinical context for each area. Features helpful learning tools for each entry, including illustrations of key concepts, mnemonics, clinical pearls; and carefully chosen study questions to encourage further study and test your knowledge. Each entry contains free online references. Helps you quickly refresh your knowledge of specific disorders and ascertain whether your patients' diagnoses satisfy Fisher's "three-of-five" rule.